Cultural Humility in Ethnopsychiatry Nursing: A Transformative Framework for Culturally Responsive and Equity-Oriented Mental Health Care - Fatma Lutfiyatus Sayyida; Anggun Novia Indah Fitri; Indi Dwi Shofi Yanti (Interdisciplinary Journal of Ethnopsychiatric Nursing, 2025)
Cultural humility has gained recognition as a transformative framework in ethnopsychiatry nursing, offering a more reflective and equity-oriented alternative to traditional cultural competence models. This study explores how cultural humility defined as a lifelong process of self-reflection, learning, and mutual respect can enhance mental health care for culturally diverse populations, including refugees, racial minorities, and Indigenous communities. A systematic literature review and thematic synthesis were conducted to identify key dimensions of cultural humility and its implications for clinical practice, education, and institutional reform. Six core themes emerged: enhancing therapeutic relationships through self-reflection; addressing systemic inequities and power dynamics; improving communication and treatment engagement; facilitating holistic and culturally responsive care; institutionalizing cultural humility; and navigating implementation challenges. Findings indicate that cultural humility supports more accurate assessments, stronger therapeutic alliances, and inclusive care environments that honor patients' identities and lived experiences. Moreover, embedding cultural humility into nursing curricula and organizational policies can drive systemic change and reduce disparities in mental health outcomes. Despite barriers such as resistance to change and limited resources, strategic implementation through leadership support, training, and policy reform can foster sustainable improvements in patient-centered care. This review underscores the importance of cultural humility as a foundational approach for advancing equity, improving clinical effectiveness, and promoting social justice in ethnopsychiatry nursing.